A global review of the impact of forest property rights interventions on poverty. (January 2021) - Miller, Daniel C.; Rana, Pushpendra; Nakamura, Katia; Irwin, Samantha; Cheng, Samantha H.; Ahlroth, Sofia; Perge, Emilie
Highlights: Review of evidence on forest property rights intervention poverty impacts worldwide. Evidence includes 61 articles comprising 91 case studies across 24 countries. Only 11 articles (22 cases) used methods to control for potential confounding factors. Reported poverty impacts generally positive or mixed, but subject to high risk of bias. Rigorous impact evaluation and qualitative studies needed to draw broader conclusions. Abstract: Secure property rights are widely understood as critical for socio-economic development and sustainable land management in forested areas. Policies and programs, ranging from devolution of specific resource rights to formal land titling, have therefore been implemented to strengthen forest tenure and property rights in countries around the world. Despite the prevalence and importance of these efforts, however, systematic understanding of their effects on poverty remains lacking. We address this gap by systematically reviewing evidence on the impact of forest property rights interventions on poverty worldwide. We drew from a systematic map of evidence on forest-poverty links (Cheng et al., 2019 ) and used a population-intervention-comparator-outcome (PICO) framework to identify relevant studies. Our final dataset included 61 articles published from 2002 to 2016 comprising 91 case studies across 24 countries. Of these, only 11 articles (22 cases) used quasi-experimental methods to control for confounders. We find that almost all studied interventions (n = 88; 97%) focused on rights to access a forest area or withdraw resources from it. Relatively few studied interventions supported the more extensive property rights of exclusion (32%) and alienation (10%). Overall, reported impacts on both income/consumption and capital/assets dimensions of poverty were generally positive or mixed. Results from more robust quasi-experimental assessments showed greater variation, with case studies as likely to report negative as positive impacts on both poverty dimensions. We find tentative support for the economic theory that more secure property rights yield positive welfare effects. However, the paucity of evidence from more robust impact assessments constrains our ability to draw generalizable conclusions about the poverty impacts of different kinds of forest property rights interventions.